More answers

Lvl 10

21

The equivalent expression of 10x-11x is -x, or negative x.

The answer to the algebraic expression of 10x-11x is -x.

Equivalent expression answer to 10x-11x is simply -x.

Q: Equivalent expression Answer 10x 11x

Write your answer...

Submit

Still have questions?

Related questions

22

11x = 10x-19 Subtact 10x fromboth sides:- x = -19

22

-11x-1 = -10x-8 -11x+10 = -8+1 -1x = -7 x = 7

-10x = x-33 -10x-x = -33 -11x = -33 x = 11

6.10 is the solution to the equation 10x (6.11x) 6.

10x-7+x+7 = 11x

Add -x -6y. Just like with numbers, subtract the first from the second to find what to add to the first to get the second; keeping like terms together: (10x - 4y) - (11x + 2y) = (10x - 11x) + (-4y - 2y) = (10 - 11)x + (-4 - 2)y = -x - 6y

Isolate the variable. Get it by itself. 9+11x=89+x 9+11x-1x=89+x-1x Subtraction property of equality 9+10x=89 9+10x-9=89-9 subtraction property of equality 10x=80 x=8 division property of equality.

12x - 5 = 11x + 5(1) add 5 to both sides:12x - 5 + 5 = 11x + 5 + 512x = 11x + 10(2) next subtract 11x from both sides:12x - 11x = 11x - 11x + 10x = 10

Though 10x +24 is an expression and it can not be evaluate, we can write 10x+24=2 • (5x + 12)

(2x - 1)(5x + 8)